(3cJGH aj GdhYXs ((3eMeO Hf SYjO Hf YHO GdQMef GdUfgGLi s)
(3ChdgG (B:s
(3jHOC HHGH GdEjeGf hUaGJ GdeDef s
(3BNQgG (B:s
(3hjG TgQ QeVGf Ydjc efG GdSdGe ced s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdMeQI hGdUaQI hGdRQbIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJhMjO hGdedd hGdfMds